Pemeriksaan Laboratorium Penyakit Hati - Azma Rosida (Berkala Kedokteran, 2016)
Abstract: Liver as the largest glandular organ which has an important role in glucose and lipid metabolism which helps digestion, absorption of fats and fat-soluble vitamins, as well as the detoxification of the body against toxic substances. Laboratory tests often required liver disease clinician for screening and detecting of abnormalities or liver disease, to help maintaining diagnosis, to estimate the severity of the disease, to help find the etiology of a disease, assess the results of treatment, and also to help direct further diagnostic efforts and assessing the prognosis of liver disease and organ dysfunction. Interpretation of the results of liver function tests was not able to use only one parameter but also used a combination of the results examination, because the integrity of the liver cells was also influenced by factors extra hepatic. In this article discussed some liver function test is divided into three big that liver function tests, measurement of enzyme activity, and a test to look for the etiology of liver disease.Keywords: laboratory, liver disease, liver function tests Abstrak: Hati sebagai organ kelenjar terbesar memiliki peran penting dalam metabolisme glukosa dan lipid, membantu proses pencernaan, absorbsi lemak dan vitamin yang larut dalam lemak, serta detoksifikasi tubuh terhadap zat toksik.  Pemeriksaan laboratorium penyakit hati sering diminta klinisi untuk penapisan dan deteksi adanya kelainan atau penyakit hati, membantu menengakkan diagnosis, memperkirakan beratnya penyakit, membantu mencari etiologi suatu penyakit, menilai hasil pengobatan, membantu mengarahkan upaya diagnostik selanjutnya serta menilai prognosis penyakit dan disfungsi organ hati.  Interpretasi hasil pemeriksaan uji fungsi hati tidak dapat menggunakan hanya satu parameter tetapi menggunakan gabungan beberapa hasil pemeriksaan, karena keutuhan sel hati juga dipengaruhi faktor ekstrahepatik. Pada artikel ini dibahas  beberapa uji fungsi hati yang dibagi menjadi 3 besar yaitu uji fungsi hati, pengukuran aktivitas enzim, dan uji untuk mencari etiologi penyakit hati. Kata-kata kunci :laboratorium, penyakit hati, uji fungsi hati